Strategies for coping with stress most commonly used among young people overusing psychoactive substances - Makara-Studzińska, Marta; Trela, Jadwiga; Jankowska-Nowak, Renata; Grzywa-Bilkiewicz, Agnieszka (Polish Journal of Public Health, 2009)
Aim. The aim of the presented research is defining the most frequently chosen strategies of coping with stress among young people overusing psychoactive substances. Material and method. The survey covered a group of 100 people aged 14-19 overusing psychoactive substances. The control group consisted of 301 people, not treated for risk behaviour. In the study the authors used SRSS scale – Ways of Coping with Stress, which was designed by P. Oleś. Results. In the range of possibilities to cope with stress measured with the scale – Ways of Coping with Stress (SRSS), significant differences occurred between groups in the range of scales: search for a solution (RO), disorganization (DE), disregarding (BA), compensating (KO), strategy concentrated on a problem (PZS). Young people overusing psychoactive substances, much less frequently than youth from control group, looked for active ways of coping with stress, and consequently they became disorganized more frequently, disrespected and declined the significance of stressful situation. Discussion. People overusing psychoactive substances from the studied population, were more prone to external stimulates, which disperse and irritate them evoking defensive attitude. Many psychological and sociological theories emphasise, that some features of character connected with cognitive, emotional and motivating sphere infl uencing a form and quality of relations with oneself and with other people, can facilitate or even destiny to certain behaviour, including overusing psychoactive substances. Inability to cope with stress is one of qualities and states that is very often identified in this group of risk as well. Conclusions. The conducted studies confirm using in stressful situation, in the group of youth overusing psychoactive substances, the Emotionally Orientated Strategy, which aims to reduce emotions, increase tension and passive strategies of behaviour in stressful situation more frequently.